Modeling the Impacts of Climate Change on Future Vietnamese Households : A Micro-Simulation Approach - Rozenberg, Julie; Hallegatte, Stephane (World Bank, Washington, DC, 2016)
The impacts of climate change on poverty depend on the magnitude of climate change, but also on demographic and socioeconomic trends. An analysis of hundreds of baseline scenarios for future economic development in the absence of climate change in Vietnam shows that the main determinant of the eradication of extreme poverty by 2030 is the income of unskilled agriculture workers, followed by redistribution policies. Results from sector analyses of climate change impacts—in agriculture, health, and natural disasters—are introduced in each of the hundreds scenarios. By 2030 climate change is found to have a significant impact on poverty in Vietnam in about a quarter of the scenarios, with 400,000 to more than a million people living in extreme poverty just because of climate change impacts. Those scenarios in which climate change pushes the most people into poverty are scenarios with slow structural change away from agriculture, low productivity growth in agriculture, high population growth, and low redistribution levels. Conversely, in scenarios with rapid, inclusive, and climate-informed development, climate change has no impact on extreme poverty, although it still has an impact on the income of the bottom 40 percent.